2020
DOI: 10.1016/j.omtn.2020.01.020
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA KLF3-AS1 Suppresses Cell Migration and Invasion in ESCC by Impairing miR-185-5p-Targeted KLF3 Inhibition

Abstract: Esophageal squamous cell carcinoma (ESCC) is a common cancer occurring in males and females worldwide. Accumulating evidence continues to highlight the crucial roles of long noncoding RNAs (lncRNAs) in the process of tumorigenesis. However, the regulatory mechanism of lncRNAs in ESCC remains unclear. The aim of this study is to elucidate the role of lncRNA Krüppel-like factor 3 antisense RNA 1 (KLF3-AS1) in ESCC by regulating miR-185-5p and KLF3. Initially, ESCC cell spheres with stem cell-like properties were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 26 publications
1
48
2
Order By: Relevance
“…HEIH was differentially expressed in EC, and participated in the occurrence and development of EC 9 , suggesting that HEIH may be a possible therapeutic target for the treatment of EC. miR-185-5p overexpression was able to inhibit the invasion and migration of ESCC cells 19 , and KLF5 was the core regulatory factor for ESCC cells 20 . Given that, we detected HEIH, miR-185, and KLK5 expression by RT-qPCR and western blot assay in cancer and non-tumoral tissues of EC patients, and found that HEIH and KLK5 were elevated, and miR-185 was declined in EC tissues vs non-tumoral tissues (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…HEIH was differentially expressed in EC, and participated in the occurrence and development of EC 9 , suggesting that HEIH may be a possible therapeutic target for the treatment of EC. miR-185-5p overexpression was able to inhibit the invasion and migration of ESCC cells 19 , and KLF5 was the core regulatory factor for ESCC cells 20 . Given that, we detected HEIH, miR-185, and KLK5 expression by RT-qPCR and western blot assay in cancer and non-tumoral tissues of EC patients, and found that HEIH and KLK5 were elevated, and miR-185 was declined in EC tissues vs non-tumoral tissues (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…These results indicate that there is an ESCC-specific ceRNA network based on expression profiles of lncRNAs, miRNAs, and mRNAs [33]. Furthermore, similar ceRNA networks have been elucidated in numerous previous studies [10,12,14,16]. Collectively, these results strongly suggest that the supressed effect of lncRNA NEAT1 silencing on MMP2 in our present study was accomplished via the miR-1299 pathway.…”
Section: Discussionsupporting
confidence: 86%
“…For instance, lncRNA ZFAS1 is up-regulated in ESCC and promotes cell proliferation, migration, and invasion in ESCC cell lines by downregulating miR-124 and upregulating STAT3 [9]. lncRNA KLF3-AS1 is down-regulated in ESCC and inhibits tumor growth and invasion via weakening miR-185-5p-mediated inhibition of KLF3 [10]. lncRNA PANDA is upregulated in ESCC and drifts away from NF-YA to promote the expression of NF-YA-E2F1 co-regulated proliferation-promoting genes, as well as to restrict apoptosis [11].…”
mentioning
confidence: 99%
“…In mechanism, although lncRNAs lack the capacity to encode proteins, they are able to regulate gene expression through direct or indirect mechanism 37 . Previous studies have demonstrated that lncRNA regulates target gene expression by acting as a molecular sponge for miRNA through the ceRNA pattern in the progression of ESCC 38–40 . The ceRNA pattern is a typical regulatory mechanism at the posttranscriptional level and refers to that lncRNA competitively binds with miRNAs to antagonize the suppressive effects of miRNAs on mRNAs 23 .…”
Section: Discussionmentioning
confidence: 99%